Return on Assets and Capital Adequacy of Banks in Nigeria. - Apere, ThankGod Oyinpreye (Advances in Social Sciences Research Journal, 2016)
This research empirically investigated the relationship between Capital Adequacy of banks and Return on Assets of banks in Nigeria over the period 2001 to 2014.Using secondary data obtained from the Central Bank of Nigeria (CBN) statistical bulletin (2014) and World Bank (2015). Relevant econometric techniques were adopted in analysing the data for this study. Firstly the Descriptive Statistic test was conducted; Correlation test was also conducted to ascertain the strength of their relationship and it was observed that all the variables were stationary at their first differences, using the Phillip-Perron unit root test, and having determine the stationarity of the variables we further employ the Johansen Cointegration test, the Error Correction Model (ECM). The study revealed that there is a long-run significant positive relationship between capital adequacy and return on assets of banks in Nigeria over the period under review. This study therefore recommends that monetary authorities such as NDIC and CBN through their supervisory role should ensure that banks have enough capital so as to achieve increasing public confidence in the Nigerian banking sector thereby bringing increase returns on assets of the banks in particular and the financial sector in Nigeria.